GAYA BAHASA DALAM NOVEL TEENLIT TRILOGI “D’ANGEL”KARYA LUNA TORASHYNGU - Amelia Rosalina; Suryadi Suryadi; Irma Diani (Universitas Bengkulu, 2018)
The purpose of this study is to describe the quality of the language available in the novel teenager